The mechanism clarification of Ni–Mn–Fe–Ga alloys with excellent and stable functional properties - Yang, S. Y. (2013)
The functional properties, thermomechanical stability, ductility and shape memory effect of four types of two-phase NiMnGa-based high-temperature shape memory alloys were investigated, including Ni56+xMn25Ga19−x (x = 1, 2, 3, 4), Ni56Mn25−yFeyGa19 (y = 4, 8, 12, 16), Ni56Mn25−zCozGa19 (z = 4, 6, 8) and Ni56Mn25−wCuwGa19 (w = 2, 4, 8) alloys. It is found that Ni56Mn25−yFeyGa19 alloys (y > 4) exhibit the most excellent thermomechanical stability with no γ′ precipitates after thermomechanical cycling. Results further show that different alloying elements (Ni/Co/Cu/Fe) have different effects on the mechanical properties of both γ phase and corresponding two-phase NiMnGa-based alloys, which are closely related to the thermomechanical stability, ductility and shape memory effect of these alloys. The strength of Ni–Mn–Ga alloys decreases obviously with the addition of Fe, and the ductility of the alloys is effectively improved due to the formation of the most ductile γ phase with the lowest strength in Ni56Mn25−yFeyGa19 alloys. Particularly, Fe addition significantly improves shape memory effect of Ni–Mn–Ga alloys. As a result, two-phase Ni56Mn25−yFeyGa19 alloys exhibit the most excellent and stable functional properties as potential high-temperature shape memory materials.